Spectroscopic elucidation (FT-IR, FT-Raman and UV-visible) with NBO, NLO, ELF, LOL, drug likeness and molecular docking analysis on 1-(2-ethylsulfonylethyl)-2-methyl-5-nitro-imidazole: An antiprotozoal agent. (October 2020) - Manjusha, P.; Prasana, Johanan Christian; Muthu, S.; Rizwana, B. Fathima
Graphical abstract: In this present study, an amalgamation of experimental and theoretical investigation on the molecular structure, MEP, ELF, LOL, NBO, drug likeness and molecular docking study with spectroscopic investigation (FT-IR, FT-Raman and UV–vis) of Tinidazole, an anti-protozoal compound has been reported. Highlights: Optimized the molecular structure. Spectroscopic (FT-IR, FT-Raman and UV-vis) experimental data were compared with the theoretical data and assigned. NBO analysis carried out confirming charge delocalization and stability of the molecule. Surface reactivity was studied and the reactive sites were located based on Fukui indices. Ligand-protein interactions of anti-infective (Malaria), anti-fungal (Invasive aspergillosis) and anti-mycobacterial (Mycobacterium tuberculosis) activities were confirmed using molecular docking analysis. 2D protein-ligand interaction profile images have been created. Drug likeness analysis was performed to confirm the active potential pharmaceutical activity. Abstract: 1-(2-ethylsulfonylethyl)-2-methyl-5-nitro-imidazole (1EMI) C8 H13 N3 O4 S also known as Tinidazole, selected for its antiprotozoal property is extensively used for spectroscopic elucidations and computational aspects using density functional methods. Along with spectral conclusions, further investigations on fundamental reactive properties such as electrical, optical, nonlinear combined with DFT simulations were performed. Molecular docking procedure supports the results of chosen appropriate antiprotozoal agent based on ligand-protein interactions. Experimental and simulated (B3LYP/6-311++G (d, p)) IR and Raman spectra showed concurrence. NLO analysis through first order hyperpolarizability parameter helps in finding the potential of 1EMI as a good NLO candidate. Charge delocalization and the stability of the compound were discussed using natural bond orbital (NBO) analysis. Furthermore, Electron localization function (ELF), local orbital locator (LOL), and Frontier molecular orbitals (FMO) were studied. Besides, Mulliken population analysis on atomic charges, Energy gap, chemical potential, global hardness, softness, ionization potential, electronegativity, electrophilicity index along thermodynamic parameters (enthalpy, entropy and heat capacity) have been calculated. Drug likeness parameters and molecular docking approach enabled to check pharmaceutical potential and biological activity of 1EMI. The biological activity of 1EMI through ligand and protein interactions have been confirmed theoretically for the treatment of Malaria, Invasive aspergillosis and Mycobacterium tuberculosis with respect to chosen proteins. Three different activity targets and protein interactions are quite successful revealing the bond distances, intermolecular energy, binding energy and inhibition constant. 2D interaction profile image of the two maximum interacted proteins and also Ramachandran plot used to show stereochemistry of selected protein. The activities of 1EMI were studied in accordance with literature survey and the results were presented.